When the war never ends : the voices of military members with PTSD and their families - Wizelman, Leah (Rowman & Littlefield Publishers, 2011)
"Service members returning from deployment are often suffering from PTSD. Its symptoms include distressing flashbacks, memories and nightmares, aggression, memory problems, physical symptoms, loss of positive emotions, and withdrawal from society. When the War Never Ends tells the stories of those who have lived it themselves - affected veterans and active-duty personnel, as well as their spouses, from the U.S., Canada, Australia, and Germany, who were participants in various wars and peace missions. The stories will help family members better understand their loved ones by vividly demonstrating what a trauma survivor is feeling and going through"--Provided by publisher